Adopting an Islamic Political System In Nigeria: A Vital Means For Addressing The Challenges of Western Democracy - Dahiru Shuni, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
This article discusses the religiosity of employees that affects the positive image of Nirmala Suri Sukoharjo Hospital public relations. Religious activities such as those carried out by the spiritual team of Nirmala Suri Hospital such as routine studies every Friday, dhuha prayers, morning dhikr every day, and during the month of Ramadan perform tadarus. In addition, the spiritual team of Nirmala Suri Hospital also held Quran reading and writing for employees who were not fluent until the prayer school for employees whose prayers were not correct, this resulted in a positive image in the eyes of the community with good service to patients. This study also discusses how Nirmala Suri's hospital public relations build an internal image related to patients, patients' families, and employees. In the external sphere, public relations visit village officials, and community leaders and hold health counseling to free examinations. This research uses a type of descriptive research with a qualitative approach. Descriptive research aims to provide an overview of a society, a certain group of people, and also an overview of the relationship of one or more symptoms that are occurring. In addition to this research using data sources, primary data is data that is directly obtained from the first data source at the research location or research object. This study also explains how public relations in handling crises is by exploring what the problem is, then digging deeper into what the problem is, and then asking for time to conduct an internal search because it involves the head of the relevant unit, especially the service manager, to be able to explain to customers who have problems.